RANCANGAN POSTER LIPAT MATERI KEANEKARAGAMAN HAYATI KELAS X SMA - Netty Dewi Yuniarsih Sihotang; Darmawati Darmawati; Yuslim Fauziah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the potential of folding poster designs in high school biology subjects for class X Biodiversity material. This research was conducted at the Bina Widya Campus, Riau University in November 2020-April 2021. This research was carried out in three stages: fields survey, processing quantitative data, and the developement of folding poster designs on biodiversity material. Based on the results of the potential analysis, survey of vegetation structure and composition on the Bina Widya campus, Riau University, can be used as folding poster for the sub-material biodiversity: the level of biodiversity.Key Words: Folding Poster, Biodiversity